Konflik dalam Gereja Korintus: Kajian Biblika Surat 1 Korintus 1:10-13 dan Relevansinya pada Gereja masa kini - Telly Makagansa; Aan an; Anita I. Tuela (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is a biblical study of the text of 1 Corinthians 1:10-13 specifically the conflict within the Corinthian church. Conflict within the church did not only occur in the Corinthian congregation, but continues to exist in the church to this day. The aim of the research is to enable the church to understand the causes of conflict within the church, as well as to answer questions about divisions within the church